THE RELATIONSHIP OF AGILE CAPABILITY, MARKETING CAPABILITY, OPERATIONAL CAPABILITY AND SME PERFORMANCE IN FnB SMEs - Claresta Nathania (Indonesian Journal of Multidisciplinary Science, 2022)
Because of the growth of MSMEs, many business owners have chosen to expand their operations to the online realm. Business owners who sign up for online delivery but don't know how to make the most of it. This research is to investigate SME capabilities that can maximize performance in the Indonesia culinary industry through the use of an online delivery service. The method employed is a quantitative method that takes descriptive research. This study will collect data through a survey method, which will be distributed online to MSME owners in Jabodetabek who already activate online order delivery as respondents. This study used SPPS and SMART PLS to process the data. The findings of this study are Marketing capability, operational capability, and SME performance are all significantly influenced by agile capability. Operational capability and SMEs' performance are significantly influenced by Agile capability. However, Operational capability has no bearing on SME performance. In future research, the author can broaden the scope of respondents to obtain data from all over Indonesia. Further research can be conducted in various industries to produce results relevant to the industry in question. This research was conducted for MSME business owners, but it is also possible to conduct research from the consumer’s perspective when looking at MSMEs that use variables. For business owners who want to start using online delivery orders, they can adapt work procedures, create clear sales targets, and benchmark against competitors. In terms of operations in improving performance, business owners can listen to customer comments and anticipate surges on big days.